MORBIDITY AND MORTALITY, STRUCTURE AND RESULTS OF BREAST CANCER SCREENING IN THE REGIONS OF KAZAKHSTAN - Arman Khozhayev; Assem Mukhtarova; Assel Karabalayeva; Kuat Sultangazin; Serzhan Yerkinov; Zhanar Kanasheva; Raissa Trigubskaya; Azhar Taigulakova (Foundations and Trends in Modern Learning, 2023)
The article deals with the epidemiological and organizational aspects of early diagnosis of breast cancer, based on its secondary prevention using a population method of active detection of this pathology in clinically asymptomatic individuals - screening. A detailed algorithm for the preventive examination of the female population is presented and the results of mammographic screening in a regional context are presented. It has been shown that the use of mammography based on the use of low-dose X-ray radiation allows a differentiated approach to diagnosis, development of management tactics and targeted treatment of these patients.